Tissue phantom study of the effect of metal nanoparticles in tissue imaging - Akshaya Deosthale (2011)
This project attempts to study the effect of metal nanoparticles, mainly silver and gold, as contrast agents on tissue imaging via Surface Enhanced Raman Spectroscopy (SERS). An effort is made to develop protocols for the synthesis of agarose tissue phantoms as well as silver nanoparticles. The Raman scattering molecules used are in the form of Rhodamine 6G (R6G) powder. To mimic the optical properties of human tissue, a light scattering component, Intralipid, and a light-absorbing component, nigrosin dye, have also been incorporated into the agarose tissue phantoms. It is shown how these silver nanoparticles and gold nanoparticles (from Sigma Aldrich) are then incapacitated into the agarose tissue phantoms in an attempt to observe enhancement of the imaging signals. Several attempts have been made to develop the protocols in order to change the size of the nanoparticles and the consistency of the phantoms for optimization of results.